Analysis of Actomyosin Oscillatory Dynamics Using a Coarse-Grained Model - Hernández-Del-Valle, Miguel; Valencia-Expósito, Andrea; Gorfinkiel, Nicole; Martín-Bermudo, Maria D.; Míguez, David G. (Frontiers in Physics, 2022)
Autonomous oscillatory dynamics are ubiquitous at every level in Biology. At the cellular level, one of the most relevant and well characterized examples of periodic behavior is the cyclic assembly and disassembly of actomyosin networks. In Drosophila, these oscillations induce the robust contraction and expansion of individual cells required for correct dorsal closure, while in the follicular epithelium that surrounds the germline, periodic contractions of the basal actomyosin network are required for proper elongation of the egg chamber. While some studies suggest that actomyosin oscillations are driven by upstream signaling or mechanochemical features, we have recently proposed that they arise as a systems property from the competition between two well characterized features of the actomyosin machinery: (1) cooperative assembly of actin networks mediated by Actin crosslinker proteins and (2) tension-induced disassembly of actin networks mediated by myosin motors. Here, we perform experiments in amnioserosa and in the follicle cells of drosophila and simulations using a coarse-grained model of the actomyosin cortex to characterize the properties of the oscillations and how they depend on different features of the system. We also compare model and experiments to study the dynamics of actomyosin flows and the effect of mechanical coupling between cells in the tissue. In conclusion, our model is a powerful tool to study key features of actomyosin oscillations, from the effect of the individual components to network properties and finally supra-cellular organization of the oscillations at the tissue level.